2005
DOI: 10.1017/s1351324905003682
|View full text |Cite
|
Sign up to set email alerts
|

Implementing clarification dialogues in open domain question answering

Abstract: We examine the implementation of clarification dialogues, a mechanism for ensuring that question answering systems take into account user goals by allowing them to ask series of related questions either by refining or expanding on previous questions with follow-up questions, in the context of open domain Question Answering systems. We develop an algorithm for clarification dialogue recognition through the analysis of collected data on clarification dialogues and examine the importance of clarification dialogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…However, we found that a straightforward extension, e.g. [1], did not work well in our project on context-based video retrieval, where the videos are typically accompanied by text descriptions such as google video. To achieve better performance, we propose a new method of computing semantic similarity between two articles based on WordNet [2], which is a concept ontology having a tree structure as shown in Figure 1(a) (See Section 2).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, we found that a straightforward extension, e.g. [1], did not work well in our project on context-based video retrieval, where the videos are typically accompanied by text descriptions such as google video. To achieve better performance, we propose a new method of computing semantic similarity between two articles based on WordNet [2], which is a concept ontology having a tree structure as shown in Figure 1(a) (See Section 2).…”
Section: Introductionmentioning
confidence: 90%
“…A straightforward method is given in [1] to combine the semantic similarity between two words to compute the semantic similarity between two articles. Given two articles P and P , their semantic similarity is computed as follows in [1] …”
Section: Similarity Calculatingmentioning
confidence: 99%
See 3 more Smart Citations